Two new coastal time-series of seawater carbonate system variables in the NW Mediterranean Sea: rates and mechanisms controlling pH changes - García-Ibáñez, Maribel I.; Guallart, Elisa F.; Lucas, Arturo; Pascual, Josep; Gasol, Josep M.; Marrasé, Cèlia; Calvo, Eva; Pelejero, Carles (Frontiers in Marine Science, 2024)
In this work, we present, for the first time, the seawater carbonate system measurements of two coastal time-series in the NW Mediterranean Sea, L’Estartit Oceanographic Station (EOS; 42.05°N 3.2542°E) and the Blanes Bay Microbial Observatory (BBMO; 41.665°N 2.805°E). At these two time-series, measurements of total alkalinity (TA), pH, and associated variables, such as dissolved inorganic nutrients, temperature, and salinity, have been performed monthly since 2010 in surface seawater. Seasonality and seasonal amplitude are analogous in both time-series, with seasonality in pHTin situ(pH at in situ seawater conditions on the total hydrogen ion scale) primarily determined by seasonality in sea surface temperature. The evaluated pHTin situtrends at BBMO (-0.0021 ± 0.0003 yr-1) and EOS (-0.0028 ± 0.0005 yr-1) agree with those reported for coastal and open ocean surface waters in the Mediterranean Sea and open ocean surface waters of the global ocean, therefore indicating that these time-series are representative of global ocean acidification signals despite being coastal. The decreases in pHTin situcan be attributed to increases in total dissolved inorganic carbon (DIC; 1.5 ± 0.4 µmol kg-1 yr-1 at BBMO and 1.6 ± 0.6 µmolESkg-1 yr-1 at EOS) and sea surface temperature (0.08 ± 0.02 °C yr-1 at BBMO and 0.08 ± 0.04 °C yr-1 at EOS). The increases in carbon dioxide fugacity (fCO2; 2.4 ± 0.3 µmol kg-1 yr-1 at BBMO and 2.9 ± 0.6 µmol kg-1 yr-1 at EOS) follow the atmospheric CO2 forcing, thus indicating the observed DIC increase is related to anthropogenic CO2 uptake. The increasing trends in TA (1.2 ± 0.3 µmol kg-1 yr-1 at BBMO and 1.0 ± 0.5 µmol kg-1 yr-1 at EOS) buffered the acidification rates, counteracting 60% and 72% of the pHTin situdecrease caused by increasing DIC at EOS and BBMO, respectively. Once accounted for the neutralizing effect of TA increase, the rapid sea surface warming plays a larger role in the observed pH decreases (43% at EOS and 62% at BBMO) than the DIC increase (36% at EOS and 33% at BBMO).